Are ableist insults secretly slurs?. (January 2020) - Cousens, Chris
Abstract: Philosophers often treat racist and sexist slurs as a special sort of puzzle. What is the difference between a slur and its correlates? In attempting to answer this question, a second distinction has been overlooked: that between slurs and insults. What makes a term count as a slur? This is not an unnecessary taxonomical question as long as ableist terms such as 'moron' are dismissed as mere insults. Attempts to resolve the insult/slur distinction by considering the communicative content of slurs are not promising. A better solution is offered by speech act theory, and this paper develops a novel way to describe ordinary slurring utterances as oppressive speech acts. This can both explain the difference between slurs and insults, and challenge the dismissal of ableist terms. Highlights: Distinguishing between 'slurs' and 'insults' is difficult to do with existing philosophical accounts of slurs. The best way to account for the insult/slur distinction is with speech act theory. Ableist insults are often mistakenly treated as insults when they have much more in common with slurs.